ALPHA AMYLASE ALPHA GLUCOSIDASE AND ANTIDIABETIC ACTIVITY OF GYMNEMIC ACID IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Khan Ayesha Tazeen; Subur Khan Wadood Khan; Dr.Syed Ayaz Ali; Barrawaz Aateka Yahya; Quadri Neha Naushin (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Diabetes is being described as one of the worldwide health problems that escalates every day. We found it difficult to discover new antidiabetic drugs from medicinal plants with minimal or no side effects. The current research study involved determining the beneficial effects of the gymnemic acid isolated from plant Gymnema Sylvester against diabetes rats induced by streptozotocin.The gymnemic acid was extracted from 75% Gymnemic acid extract of the Gymnema Sylvster plant. Rats were made diabetic through a fructose-containing drinking water mixture and a single dose of streptozotocin. The effects of gymnemic acid on blood glucose levels in blood and diabetes complications were studied after the administration of it to diabetic rats for 21 days—of four-point blood glucose testing (on days 1, 7, 14, and 21). Blood samples were collected from experimental rats at day 21 before euthanasia for collection of the pancreas and liver. Blood samples were used to establish liver function tests, kidney function test, and lipid profiles. BGL reduction on the 21st day was significant as determined using in vivo antidiabetic study while other tests for liver and kidney as well as lipid profile were normal in extract-treated groups. Gymnemic acid was found to have good inhibitory effect on the in vitro alpha-amylase and alpha glucosidase assay. Results obtained in research indicated the presence of appreciable in vitro and in vivo antidiabetic efficacies in Gymnemic Acid.